2004
DOI: 10.1182/blood.v104.11.4831.4831
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Single-Agent Lumiliximab (Anti-CD23 Antibody) in Patients with Chronic Lymphocytic Leukemia.

Abstract: CD23 is highly expressed on the cell surface of certain B-cell malignancies including chronic lymphocytic leukemia (CLL). Lumiliximab (L-mab), a macaque-human chimeric anti-CD23 antibody, has been reported to have antitumor activity against CLL in preclinical studies. In this 46 patient, Phase I, multicenter study, single-agent L-mab was evaluated as a treatment for patients with relapsed or refractory CLL. Therapy consisted of intravenous L-mab given as 6 regimens: (1) 125 mg/m2/wk for 4 weeks; (2) 250 mg/m2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a phase I trial for patients with relapsed CLL, lumiliximab demonstrated decrease in lymphocyte counts in 91% of patients and reduction in lymphadenopathy in 59% of patients. 66 This was followed by a phase I/II trial in which lumiliximab was given in combination with the FCR regimen to patients with relapsed CLL. 67 This study enrolled 31 patients and lumiliximab was administered at 375 mg/m 2 (n = 3) or 500 mg/m 2 (n = 28) in combination with FCR for six cycles.…”
Section: Targeting the Surface Moleculementioning
confidence: 99%
“…In a phase I trial for patients with relapsed CLL, lumiliximab demonstrated decrease in lymphocyte counts in 91% of patients and reduction in lymphadenopathy in 59% of patients. 66 This was followed by a phase I/II trial in which lumiliximab was given in combination with the FCR regimen to patients with relapsed CLL. 67 This study enrolled 31 patients and lumiliximab was administered at 375 mg/m 2 (n = 3) or 500 mg/m 2 (n = 28) in combination with FCR for six cycles.…”
Section: Targeting the Surface Moleculementioning
confidence: 99%